Complex Lipids of Rhodomicrobium vannielii - Park, Chong-Eel (1967)
Eight components, seven of which contained phosphorus, were found in the phospholipid fraction of Rhodomicrobium vannielii. The major components were lipoamino acid (o-ornithine ester of phosphatidyl glycerol, 46.5%) and phosphatidyl choline (26.5%). The other six components were phosphatidyl glycerol (9.7%), bisphosphatidic acid (6.7%), phosphatidyl ethanolamine (4.5%), phosphatidic acid (1.8%), lysophosphatidyl glycerol-o-ornithine ester (3.2%), and N,N-ornithine amide of unidentified fatty acid (0.95%). Total phospholipid accounted for 4.2% of cell dry weight. The major fatty acid was vaccenic acid, C(18:1), which accounted for approximately 90% of the total fatty acids of the complex lipid fraction. The other four fatty acids were C(16:0) (6.25%), C(18:0) (3.8%), C(14:0) (0.7%), and C(16:1) (0.35%). The sulfolipid content was 0.01% of the cell dry weight or 0.14 μmoles per g of dried cells, assuming that its fatty acid component is vaccenic acid. No steroids were detected.